PENGEMBANGAN MODUL FUNGI BERBASIS GROUP INVESTIGATION PADA MATA PELAJARAN BIOLOGI KELAS X SMA NEGERI 05 METRO - Rohmatika Nur Hidayati; Triana Asih; Agus Sujarwanta (EDUBIOLOCK, 2023)
The research and development aims to produce a product in the form of an investigation group-based biology learning module on mushroom material that is suitable for use as teaching materials for class X IPA SMA. The development of this module uses a Research and Development development model using a 4-D model, starting from looking for potential problems, collecting data, validating products, revising products, and testing usage products. The result of the development of a biology module based on the investigation group from the design aspect was obtained a percentage of "75.5%". The results of the material expert validation got a percentage of "90%" and the results of the student response test obtained a percentage of "87.2%". It can be concluded that the average percentage value is "84.2%" with the criteria "Very Good". So it can be concluded that the developed toothpaste is suitable for use as a reference for teaching materials in biology learning on mushroom material in schools.